2023
DOI: 10.1002/smll.202304118
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ion Beam Synthesis of Ultra‐Fine Molybdenum Carbide Nanoparticles: Toward a Scalable Fabrication Route for Earth‐Abundant Electrodes

Abstract: Molybdenum carbides are promising low‐cost electrocatalysts for electrolyzers, fuel cells, and batteries. However, synthesis of ultrafine, phase‐pure carbide nanoparticles (diameter < 5 nm) with large surface areas remains challenging due to uncontrollable agglomeration that occurs during traditional high temperature syntheses. This work presents a scalable, physical approach to synthesize molybdenum carbide nanoparticles at room temperature by ion implantation. By tuning the implantation conditions, variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The measurement of the composition and phase of the implanted samples by RBS, XPS, GIXRD, and STEM provides important mechanistic insights into tungsten carbide formation by ion implantation. In our previous work, we showed that molybdenum carbide nanoparticles of different phases and sizes can be accessed by ion implantation . We elucidated the role played by collision cascades and thermal spikes in determining the nanoparticle phase and size.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The measurement of the composition and phase of the implanted samples by RBS, XPS, GIXRD, and STEM provides important mechanistic insights into tungsten carbide formation by ion implantation. In our previous work, we showed that molybdenum carbide nanoparticles of different phases and sizes can be accessed by ion implantation . We elucidated the role played by collision cascades and thermal spikes in determining the nanoparticle phase and size.…”
Section: Resultsmentioning
confidence: 97%
“…Traditional TMC syntheses require a transition metal, carbon-based gaseous precursors, and high temperatures (>900 K) to achieve carburization. , High temperatures and long synthesis times cause agglomeration of initially formed nanoparticles and coking, ultimately lowering the surface area and catalytic performance of the synthesized carbide materials . Other pyrolysis-based syntheses use expensive or toxic metal complexes such as W­(CO) 6 and Cp 2 W 2 (CO) 4 (DMAD) with long carburization periods (>12h). , Alternative methods using a microwave furnace and ion implantation have been shown to avoid particle agglomeration while maintaining phase control and industrial scalability, ultimately leading to highly active nanostructured transition metal carbides. , The ultrafast cooling periods (>10 4 K s –1 ) also allow metastable phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing orbital hybridization between the 1s orbital of the H atom and the 4d z 2 orbital of the Mo atom forms a weaker σ bond, thus aligning Δ G H* with the Sabatier principle . This highly active carbide surface is facilitated by the unique synthesis conditions that are realized through ion implantation …”
Section: Resultsmentioning
confidence: 99%
“…30 This highly active carbide surface is facilitated by the unique synthesis conditions that are realized through ion implantation. 19 To understand the underlying mechanism of HER on the MC catalysts, Tafel plots were created from the polarization curves.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation